Early muscular fitness adaptations in children in response to two different resistance training regimens - Faigenbaum, A.; Milliken, L.; Moulton, L.; Westcott, W. L. (Pediatric Exercise Science, 2005)
The purpose of this study was to compare early muscular fitness adaptations in children in response to low repetition maximum (LRM) and high repetition maximum (HRM) resistance training. Twenty-three girls and 20 boys between the ages of 8.0 and 12.3 years (mean age 10.6 ± 1.3 years) volunteered to participate in this study. Children performed one set of 6 to 10 RM (n = 12) or one set of 15 to 20 RM (n = 19) on child-size exercise machines twice weekly over 8 weeks. Children in the control group (n = 12) did not resistance train. Maximum strength (1 RM) on the chest press, local muscular endurance (15 RM) on the leg press, long jump, vertical jump, and v-sit flexibility were assessed at baseline and posttraining. The LRM and HRM groups made significantly greater gains in 1 RM strength (21% and 23%, respectively) as compared with the control group (1%). Only the HRM group made significantly greater gains in 15 RM local muscular endurance (42%) and flexibility (15%) than that recorded in the control group (4% and -5%, respectively). If children perform one set per exercise as part of an introductory resistance training program, these findings favor the prescription of a higher RM training range.